Social entrepreneurship mengatasi krisis sosial dan ekonomi di masa Covid-19: perspektif ekonomi islam - Vania, Adek; Anwar, Saiful (Jurnal Paradigma Ekonomika, 2022)
The COVID-19 pandemic has impacted the world’s economic and social crisis. The implementation of Social Distancing causes a fundamental change in the community’s social behavior and a decrease in the level of the economy due to restrictions on mobility and economic activities. Difficulties from the government and industry to rise must be encouraged by initiatives and breakthroughs from the community to grow together with the emergence of social solidarity. Starting from this sense of empathy and concern, this paper analyzes the importance of developing social entrepreneurship and its supporting elements, namely altruism and social capital or trust, in realizing sustainable economic goals in overcoming the current social and economic problems. Using a literature review approach with content and comparative analysis approach, this article on the perspective of social entrepreneurship will touch on the paradigm of classical/conventional capitalist economic theory, which has the opportunity to be perfected by Islamic Economics. It is time for the economy to prioritize a socially oriented approach rather than a money-oriented one. So it is hoped that it will foster a sense of empathy and spread kindness which is a reflection of Islamic religious values, namely the principle of justice and the benefit of the people, as the ultimate goal to go to Falah (the glory of life in this world and the hereafter).